The Role of Online Learning Platforms in Supporting Inclusive Education in Indonesia - Rangkuti, Zulkifli; Yahya Obaid, Moh.; Sonjaya, Iwan; Tahir, Muhammad; Setiyatna, Hery (Mandalika Institute, 2026)
Inclusive education is a central goal in creating equitable education systems; however, Indonesia continues to face challenges related to learner diversity, socio-economic disparities, and geographical inequalities. The expansion of online learning platforms offers opportunities to foster more inclusive learning environments. This study explores the role of online learning platforms in supporting inclusive education in Indonesia using a qualitative literature review approach. Academic publications from 2018–2025 were systematically selected, and ten core articles were analyzed through thematic analysis. The findings indicate a moderate to significant impact of online learning platforms on inclusive education, particularly in enhancing accessibility, instructional flexibility, and personalized learning for diverse learners. When integrated with inclusive pedagogical strategies, digital platforms also contribute to increased student engagement and participation. Nevertheless, major challenges persist, including digital divides, limited teacher digital competence, uneven infrastructure, and policy–practice gaps. The study concludes that optimizing digital-based inclusive education requires targeted infrastructure investment, continuous teacher training in inclusive digital pedagogy, and stronger alignment between policy and practice.